English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

show me the working for this sum please

2006-11-01 08:58:31 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

Hello again darling

3(m-2)-(m=4)=8

● Step 1
3(m-2) =
(3 * m) + (3 * -2 ) =
3m - 6

● Step 2
-(m - 4)=
-m + 4

● Step 3
3m - 6 - m + 4 = 8
( 3m - m ) = 8 +6 - 4
2m = 10
m = 10 / 2
m = + 5

Good Luck Sweetheart ♣

2006-11-01 09:04:17 · answer #1 · answered by sweetie 5 · 7 0

I'm not sure what you mean by contradition...

Orginal equation:
3(m - 2) - (m - 4) = 8

Distributing the 3 and the -1 through:
3m - 6 - m + 4 = 8

Combining like terms:
2m - 2 = 8

Add 2 to both sides:
2m = 10

Divide both sides by 2:
m = 5

2006-11-01 17:01:34 · answer #2 · answered by Puzzling 7 · 1 0

Distributive property:
3m-6-m+4=8
2m-2=8
2m=10
m=5

Check:
3(5-2)-(5-4)=8
3(3)-1=8
9-1=8
8=8

2006-11-01 17:16:28 · answer #3 · answered by Anonymous · 0 0

3(m - 2) - (m - 4) = 8
3m - 6 - m + 4 = 8
2m - 2 = 8 ( Add 2 to both sides)
2m = 10
m = 5

Check:
3(5 - 2) - (5 - 4) = 8
3(3) - (1) = 8
9 - 1 = 8
8 = 8
QED

2006-11-01 17:48:42 · answer #4 · answered by CSUFGrad2006 5 · 0 0

fedest.com, questions and answers